Pengaruh Single Leg Propioceptive Exercise terhadap Keseimbangan Statis dan Dinamis pada Mahasiswa Usia 18-24 Tahun dengan Aktivitas Fisik Rendah - Adani, Maushaly; , Arif Pristianto, SSt.FT.,M.Fis; , Wijianto,SST.FT.,M.Or (2017)
Background: All facilities modern era make people choose things that easy and simple. Sedentary life style / low physical activity were formed in society, including college students. Based on RISKESDAS (2013), the proportion low physical activity aged 18-24 years old is quite high 33.25%) compared to other age groups. As result, decrease body's functional ability as static and dynamic balance. The prevention action is doing exercises, either single leg propioceptive exercise, which sent propioception afferent input to central nervous, can change efferent response to achieve balance. Research Aims: Determine effecf of single leg propioceptive exercise to static and dynamic balance in college students aged 18-24 years old with low physical activity.Method: Quantitative research with pre-experimental design, using pre and post-test two group design. Use urposive sampling. Total sample are 15 people.Result: Based on Wilcoxon Signed Ranks Test, p-value = 0.012 means influence static balance, and Paired t-test, p-value = 0.000 which is influence dynamic balance. To examine difference influences between groups is used Mann Whitney test, p-value = 0.015 means there's difference effect of single leg propioceptive exercise to increase static and dynamic balance in college students aged 18-24 years old with low physical activity. Conclusion: There is effect of single leg propioceptive exercise to static and dynamic balance in college students aged 18-24 years old with low physical activity, and there are differences in effect between two groups.